Ontogeny and individual heterogeneity of the corticosterone stress response in a wild altricial seabird, the snow petrel (Pagodroma nivea) - Angelier, Frédéric; Wingfield, John C.; Barbraud, Christophe; Parenteau, Charline; Trouvé, Colette; Chastel, Olivier (Frontiers in Ecology and Evolution, 2022)
In the current context of global change, there is evidence of a large inter-individual variability in the way animals physiologically respond to anthropogenic changes. In that context, the Hypothalamus-Pituitary-Adrenal (HPA) axis and the corticosterone stress response are of primary importance because they are thought to govern the ability of individuals to adjust to stress. Several studies have reported that this stress response is variable among adults and they have successfully linked this variability with abiotic and biotic factors. However, the inter-individual variability of the glucocorticoid stress response has rarely been examined during the developmental phase in wild vertebrates, and its potential ecological determinants remain unclear. In this study, we examined the ontogeny of the corticosterone stress response in an altricial seabird species (i.e., how corticosterone levels increase in response to a standardized stress protocol), the Snow petrel. We reported a strong heterogeneity of the corticosterone stress response at all ages in snow petrel chicks (11-, 20-, and 37-days old chicks). Although the magnitude of this corticosterone stress response varies with the age of the chick, we also found that this corticosterone stress response was repeatable throughout the post-hatching developmental period (repeatability: r > 0.50 for stress-induced corticosterone levels after a 30-min restraint). Importantly, this glucocorticoid stress response was negatively associated with the body condition of the chicks (i.e., mass corrected for body size), and previous exposure to stress was associated with a dampened corticosterone stress response. However, we did not find any link between parental traits (parental condition or parental corticosterone stress response), nest quality, hatching date, and the chick’s corticosterone stress response. Our study suggests that the corticosterone stress response is probably a consistent individual trait that is affected to some extent by post-natal conditions, and which differs among individuals very early in life.